Study of Textural and Petrographic Features in Mansehra Granite, Pakistan: Implications on Gamma Radioactivity and Dose Rates - Anees, M.; Wajid, A. A.; Qureshi, A. A.; Jadoon, I. A. K.; Manzoor, S.; Atique, A.; Masood, A. (The Nucleus, 2016)
Assessment of natural radionuclides and annual effective dose rate in Granite from Mansehra Pakistan has been carried out in this work. Overall, Mansehra Granite possess porphyritic fabric with primary minerals observed in petrography include quartz, microcline, plagioclase, biotite, muscovite etc. The study area was categorized into four zones on the basis of megascopic and microscopic features of the granite. One of the zones contained higher proportions of dark minerals like biotite, zircon, magnetite and tourmaline. This zone yielded slightly higher values of specific activities of 226Ra, 232Th and 40K; i.e. 29.27, 51.89 and 942.66 Bq kg-1 respectively and annual effective dose rate of 0.96 mSv y-1 . When comparing with the average values of specific activities of 226Ra, 232Th and 40K and total annual effective dose from granite from around the world it was found that overall, Mansehra granite does not pose a radiological hazard. Mansehra Granite is found to be safe and can be used as a building material. It is however, emphasized that construction of basements in the area of high activity should be avoided and granite from such areas may be used on a limited scale.